A tale of two data sets: comparing German administrative and survey data using wage inequality as an example - Heiko Stüber; Markus M. Grabka; Daniel D. Schnitzlein (Journal for Labour Market Research, 2023)
Abstract The IAB’s Sample of Integrated Labour Market Biographies (SIAB) and the Socio-Economic Panel (SOEP) are the two data sets most commonly used to analyze wage inequality in Germany. While the SIAB is based on administrative reports by employers to the social security system, the SOEP is a survey data set in which respondents self-report their wages. Both data sources have their specific advantages and disadvantages. The objective of this study is to describe and compare the evolution of wage inequality for these two types of data. For this purpose, different sample restrictions are applied. The comparison without any harmonization of the data shows different levels and trends. When the information is largely harmonized, comparable trends and similar levels emerge.